Minimally invasive ultrasound-guided biopsy of the common extensor tendon enthesis: a cadaveric study to standardise the technique - Rizzo, Chiara; Coronel, Luis; De Lorenzis, Enrico; Rubortone, Pietro; Möller, Ingrid; Miguel Perez, Maribel; Tur, Carlo; Raimondo, Maria Gabriella; Belmonte, Beatrice; Cancila, Valeria; Ramming, Andreas; Schett, Georg; et al. (RMD Open, 2025)
OBJECTIVE: To develop and validate a minimally invasive ultrasound (US)-guided biopsy technique to collect entheseal tissue from the common extensor tendon (CET) enthesis at the lateral humeral epicondyle. METHODS: Seven sonographers performed a US examination of the CET on six human cadaveric upper limbs to locate the enthesis using an anatomical landmark-based approach. An adapted mini-arthroscopic system was introduced under US guidance to the target site for sample collection. At the end of the procedure, a dye was injected through the guide needle, followed by dissection, to confirm the sampling location. Histology and immunohistochemistry analyses were performed to assess the quality and representativeness of the samples. The reliability of the procedure among operators was evaluated by analysing the rate of successful sampling. RESULTS: 24 samples were collected. The target site to be biopsied was identified as the insertion of the extensor carpi radialis brevis component of the CET. On dissection, the stain used to verify sampling accuracy was confirmed within the defined target area, with no damage to adjacent structures. Histology and immunohistochemistry indicated that most of the samples exhibited characteristics consistent with entheseal tissue (21 out of 24). All participants identified the CET and successfully completed the procedure, demonstrating reliable sample quality across operators. CONCLUSION: We developed a landmark-based approach to perform a minimally invasive full controlled US-guided biopsy of the CET enthesis that showed to be feasible and reproducible. We believe that this standardised, minimally invasive technique will widespread a reliable collection of entheseal tissue for future clinical and translational studies.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Arthritis; Psoriatic; Tendinopathy; Ultrasonography